Making Visible Alternative Futures on Mine- Scarred Lands in Appalachia - Butler, Peter; Campbell, Angela; Chu, Jing; Hosogaki, Ayaka; Riley, Adam (ARCC Conference Repository, 2013)
The Southern Coalfields of West Virginia is a region under going extraordinary levels of change through the practice of mountaintop removal mining (Todd 2008). At the core of the disturbance is northern McDowell County in deep southern West Virginia, an economically and ecologically compromised area long dependent on extractive industries, and a venue of ongoing degradation. Mountaintop removal involves the excavation of a coal seam from the top down, rather than traditional tunnel mining. As ‘developable’ flat land,the remnant landscape is perceived to provide economic development opportunities for local communities. The ‘site’ (6000 acres) of this project is a reclaimed surface mine north of the town of Welch WV and on the border between Wyoming and McDowell Counties including the Indian Ridge Industrial Park (600 acres). This project proposes the positive reuse of the landscape through the installation of alternative energy infrastructure: biomass, wind and solar; and a phased plan for integration of mixed-use development. In visualizing change within the project area researchers created a three-dimensional digital model of thesite using ground-based static and aerial LiDAR (Light Detection and Ranging). The model provides a very recent (2012) portrait of the landscape and its components: bare-earth topography; drainage systems installed as a part of the reclamation mitigation; groundcover, shrub layer, sub-canopy and canopy vegetation; infrastructure, roads, and buildings. The lone resident buildings on the site are components of a Federal Correctional Institution (FCI-McDowell). Designing within the model allowed researchers to test avariety of planning scenarios and create visualizations that captured the phasing of the project, and expressed the aspirations of the community. Visualization phases included: 1.Biomass, Solar, Wind andRecreation; 2.Expressway Development and Interchange Zone; 3.Residential; 4.Commercial and Industrial;and 5.Stormwater Infrastructure, Green Infrastructure and Bioremediation. Local participation ensured thatthe project addressed local needs in becoming a model project for the region promoting sustainable development approaches to heavily impacted landscapes.